The The Transformation of Islamic Boarding School Learning in the Digital Era - Ahmad Zacky Burhani; Herdianto Wahyu Pratomo; Nurhidayat Nurhidayat (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic boarding school is an Islamic educational institution that plays a strategic role in shaping the character, morals, and intellectual development of its students through an education system based on Islamic values and classical teaching traditions. However, the development of digital technology requires Islamic boarding school to adapt to remain relevant in answering the challenges of the Times. This study aims to examine the integration of digital technology in the boarding school education system by exploring the potential, challenges, and implementation strategies of digital transformation that are based on the traditional values of boarding schools. The study used a qualitative approach through literature studies, case analysis, semi-structured interviews, and field observations, with triangulation techniques to maintain data validity. The results show that the digitization of Islamic boarding school has great potential in expanding access to learning materials, improving administrative efficiency, and opening up opportunities for collaboration and global networking. On the other hand, the implementation of technology faces challenges in the form of limited digital literacy, infrastructure, and financing constraints, as well as concerns about the erosion of traditional Islamic boarding school values. The case study of Darunnajah Islamic boarding school in Jakarta shows that a planned digital transformation, supported by the development of human resources, technological infrastructure, and commitment to maintaining tradition, is able to improve the quality of learning and governance of the Islamic boarding school. This study recommends an integrative and contextual digital transformation strategy as an effort to realize an adaptive, innovative, and still firmly rooted Islamic boarding school in Islamic values.